Development of a diabetic retinopathy screening model for a district health system in Limpopo Province, South Africa - Abdool, Zaheera; Naidoo, Kovin; Visser, Linda (African vision and eye health, 2022)
BackgroundDiabetes mellitus (DM) and diabetic retinopathy (DR) are important issues in the district health system (DHS) of South Africa (SA). Guidelines for the management of DR in SA were developed more than a decade ago but not effectively implemented.AimThe aim of this study was to develop a suitable model for DR that could be effectively implemented by a team of healthcare practitioners (HCPs) to co-manage DM and DR in the DHS of SA.SettingThe study was conducted through Voortrekker District Hospital, Limpopo Province, SA.MethodsA saturated strategy sample study was employed, and questionnaires were distributed to 24 endocrinologists in both private and public practices in Gauteng Province and to three ophthalmologists and 10 medical officers (MOs) in ophthalmology in health institutions in Waterberg and Capricorn districts of Limpopo Province. The questionnaires distributed included questions relating to the recommended roles of primary healthcare (PHC) nurses, MOs in general practice, MOs in ophthalmology, ophthalmic nurses, optometrists, and ophthalmologists to manage patients with DM in the public sector. The Delphi technique was employed requiring experts to comment qualitatively and quantitatively to elicit the required information.ResultsAt PHC level, PHC nurses are to document a comprehensive patient case history and assess vitals before referring to MOs in general practice. Medical officers in general practice are to assess DM control and screen for target organ disease. All patients with DM are to be referred to optometrists for retinal photography. Optometrists and ophthalmic nurses are to detect, grade and monitor pre-proliferative stages of DR, and refer to MOs in ophthalmology or ophthalmologists at district or tertiary hospitals for surgical intervention or treatment.ConclusionBased on the expertise of the endocrinologists and ophthalmologists concerned, a DR screening model for a DHS was proposed, reflecting the role of HCPs in the management of DM and DR in the DHS of Limpopo Province, SA.